Defaulting alone: The geography of SME owner numbers and credit risk in Hungary - Csaba Burger (Magyar Nemzeti Bank, 2022)
The transition from the state ownership to market mechanisms in Hungary fundamentally altered the geography of domestic micro, small, and medium enterprises (SMEs). This study investigates the spatial and temporal evolution of owner numbers, using data on all Hungarian SMEs between 1991 and 2019 and across 175 regional districts. Then it explores the relationship between the number of owners and the probability of credit default by joining data from the Credit Registry (KHR) for the period between 2007 and 2019. The number of owners at an average SME sank from four in 1991 to two in 2019, with consistently higher averages in less populated regions. Meanwhile, SMEs with one owner only have up to twice as high credit default probability as SMEs with more owners over all geographies in all years. Therefore, regionally varying ownership structures mean regionally differing ownership and management practices and hence risk levels. These could be mitigated with targeted regional policy measures.
Keywords: G21; G3; R3; R11; R1; 330; financial geography; ownership structures; credit risk; SMEs